2009
DOI: 10.1016/j.gca.2008.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Silicon isotopic fractionation during adsorption of aqueous monosilicic acid onto iron oxide

Abstract: The quantification of silicon isotopic fractionation by biotic and abiotic processes contributes to the understanding of the Si continental cycle. In soils, light Si isotopes are selectively taken up by plants, and concentrate in secondary clay-sized minerals. Si can readily be retrieved from soil solution through the specific adsorption of monosilicic acid (H 4 SiO 4 0 ) by iron oxides. Here, we report on the Si-isotopic fractionation during H 4 SiO 4 0 adsorption on synthesized ferrihydrite and goethite in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
141
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(154 citation statements)
references
References 63 publications
11
141
2
Order By: Relevance
“…However, the isotope composition of the bSiO 2 seemed to remain constant within the reactive surface layer where most of the dissolution and precipitation occurred, which makes isotopic fractionation during dissolution unlikely. From leaching experiments on older Pleistocene and Pliocene sediments, Tatzel et al (2015) report that the formation of authigenic Al-Si phases should be 2‰ lighter than the pore waters they formed from, in agreement with previous experimental results (Delstanche et al, 2009;Geilert et al, 2014;Oelze et al, 2014Oelze et al, , 2015. However, the authors observed an increase of the Si isotope composition of the preserved SiO 2 during phase transformation from opal-A to opal-CT.…”
Section: Pore Water and Biogenic Silica Preservationsupporting
confidence: 78%
See 1 more Smart Citation
“…However, the isotope composition of the bSiO 2 seemed to remain constant within the reactive surface layer where most of the dissolution and precipitation occurred, which makes isotopic fractionation during dissolution unlikely. From leaching experiments on older Pleistocene and Pliocene sediments, Tatzel et al (2015) report that the formation of authigenic Al-Si phases should be 2‰ lighter than the pore waters they formed from, in agreement with previous experimental results (Delstanche et al, 2009;Geilert et al, 2014;Oelze et al, 2014Oelze et al, , 2015. However, the authors observed an increase of the Si isotope composition of the preserved SiO 2 during phase transformation from opal-A to opal-CT.…”
Section: Pore Water and Biogenic Silica Preservationsupporting
confidence: 78%
“…reviews of Opfergelt and Delmelle, 2012;Frings et al, 2016), Figure 1, Supplementary Table 1 and references therein). Adsorption of silicic acid onto Fe oxy-hydroxides (Delstanche et al, 2009) and Al hydroxides (Oelze et al, 2014) has also been demonstrated to preferentially immobilize the lighter Si isotopes. As discussed in section Rivers, all these processes are particularly complex on seasonal to geological timescales and explain most of the higher δ 30 Si DSi of continental waters.…”
Section: Weatheringmentioning
confidence: 99%
“…No chromatographic or MAGIC preconcentration steps are to be expected on such samples, since salinity is low and DSi contents are usually high. This method could also expand the studies of Si adsorption-desorption processes in batch experiments on sediments (e.g., Van Cappelen et al 2002) and soils (Delstanche et al 2009). It should permit more particularly the measurement of low rates on short time scales.…”
Section: Comments and Recommendationsmentioning
confidence: 99%
“…Alternatively, silica may have been transported to deeper water BIFs via the 'iron shuttle' (Fischer and Knoll, 2009) by adsorption on Fe-oxide/hydroxide particles and accompanying Si isotope fractionation (c.f. Delstanche et al, 2009) leading to the progressive enrichment of heavy Si isotopes in the ambient water.…”
Section: Silica Cycling and Si Isotopes In Precambrian Oceansmentioning
confidence: 99%